Perspectives of using sodium alginate with different molecular weight in the complex cancer therapy - O. Y. Rybalkina (Scientific Сentre for Family Health and Human Reproduction Problems, 2014)
The article presents the results of screening research of influence of sodium alginate with different molecular weight on the development of transplantable tumor in mice and the effectiveness of cytostatic treatment. It was determined that sodium alginates with both high (М = 403 kDa) and low (M = 1-10 kDa and M = 1 kDa) molecular weight suppress growth of Ehrlich ascites carcinoma; using sodium alginate (M = 20-30 kDa) in the scheme of chemotherapy increases effectiveness of treatment. Alginates with low molecular weight arrest development of dissemination of Lewis lung carcinoma and sodium alginates (M = 403 kDa and M = 20-30 kDa) in combination with cyclophosphan increase its antimetastatic effect.